Proton ceramic fuel cell composed of oxygen site F-doped perovskite electrode and electrolyte
The preparation of oxygen site F doped perovskite electrodes and electrolyte materials through solid phase method solves the problem of insufficient performance of existing proton ceramic fuel cell electrodes and electrolytes, significantly improves the catalytic activity and ion migration capabilities of the battery, and improves the output power density and stability of the battery.
Patent Information
- Application Number
- CN202411144399.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2025-03-11
AI Technical Summary
The electrochemical and ion transport performance of electrode materials and electrolyte materials of existing proton ceramic fuel cells need to be further improved to extend battery life and reduce costs.
The solid phase method was used to prepare the oxygen site F-doped perovskite electrode material BaCo0.4Fe0.4Zr0.1Y0.1O2.9-δF0.1 and the electrolyte material BaZr0.1Ce0.7Y0.1Yb0.1O2.9-δF0.1, and the electrolyte material BaZr0.1Ce0.7Y0.1Yb0.1O2.9-δF0.1, which was obtained by ball milling and multiple calcining.
The catalytic activity and ion mobility of oxygen electrodes and electrolytes are improved, the electrochemical impedance of the battery is significantly reduced, the performance stability and structural stability of the battery are improved, and the output power density is achieved.
Smart Images

Figure CN119601683A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a proton ceramic fuel cell composed of an oxygen site F-doped perovskite electrode and an electrolyte, belonging to the technical field of fuel cells. Background Art
[0002] Solid oxide fuel cell (SOFC) is an energy conversion device that can convert the chemical energy of fuel into electrical energy. Due to its extremely high energy conversion efficiency, wide range of fuel selection, and clean and pollution-free characteristics, it has attracted widespread attention from the world in recent years. The development and utilization of SOFC technology can effectively optimize my country's energy structure and reduce the environmental pollution caused by traditional thermal power generation. Driven by my country's "dual carbon" strategic goals and the market, the industrialization and application prospects of SOFC are bright. The insufficient life of SOFC is the bottleneck restricting its industrialization. At present, the life of SOFC can reach 40,000 hours, which needs to be extended to more than 80,000 hours to further reduce costs. The development of SOFC towards low temperature is the only way to accelerate its industrialization. Low temperature can greatly extend the service life of the battery, while reducing the difficulty of battery packaging and reducing the system cost. With the development of SOFC technology, the operating temperature of the battery has dropped to below 650℃. The development of proton conductor solid oxide fuel cell (PCFC) technology has reduced the operating temperature to 350℃, effectively promoting its industrialization process and making it a trend of SOFC industrialization development. Although PCFC has great commercial value, in terms of its current development status, the electrochemical properties and ion transport properties of its electrode materials and electrolyte materials need to be further improved. Summary of the invention
[0003] The purpose of the present invention is to provide a proton ceramic fuel cell composed of an oxygen-site F-doped perovskite electrode and an electrolyte, and a preparation method and application thereof, thereby improving the performance and stability of the proton ceramic fuel cell.
[0004] A proton ceramic fuel cell oxygen electrode perovskite material, whose chemical formula is BaCo 0.35+m Fe 0.35+n Zr 0.05+ x Y 0.05+y O 2.9-δ- F 0.05+z (BCFZYF), where δ is the oxygen vacancy content;
[0005] 0≤m,n,x,y,z≤0.1.
[0006] The above-mentioned method for preparing the perovskite material is prepared by a solid phase method.
[0007] The solid phase method comprises the following steps: ball milling BaCO3, CO3O4, Fe3O4, ZrO2, Y2O3 and BaF2 according to a stoichiometric ratio, drying and calcining to obtain an electrode material.
[0008] The rotation speed of the ball milling process is 200-600 rpm, and the calcination process parameters are: first calcining at 1100-1300°C for 5-10h, then grinding the calcined powder with a mortar, and then calcining at 1100-1300°C for 5-10h.
[0009] A proton ceramic fuel cell electrolyte material, whose chemical formula is BaZr 0.05+x Ce 0.65+p Y 0.05+y Yb 0.1 O 2.9-δ F 0.05+z (BZCYYbF), where δ is the oxygen vacancy content.
[0010] 0≤p,x,y,z≤0.1.
[0011] The preparation method of the electrolyte material is prepared by a solid phase method.
[0012] The solid phase preparation process comprises: ball milling BaCO3, ZrO2, CeO2, Y2O3, Yb2O3 and BaF2 according to a stoichiometric ratio, drying and calcining to obtain an electrolyte material.
[0013] The rotation speed of the ball milling process is 200-600 rpm, and the calcination process parameters are: calcination at 1100-1300°C for 5-10 hours.
[0014] A proton ceramic fuel cell, wherein the oxygen cell comprises the above-mentioned oxygen electrode perovskite material, and / or the electrolyte is the above-mentioned electrolyte material.
[0015] In the fuel cell, the hydrogen electrode is a composite electrode material composed of NiO and the above electrolyte material; the mass ratio of NiO to the electrolyte material is 4-6:6-4.
[0016] Beneficial Effects
[0017] Oxygen-site F-doped perovskite oxide BaCo was obtained by solid-state method. 0.4 Fe 0.4 Zr 0.1 Y 0.1 O 2.9-δ F 0.1 With BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O2.9-δ F 0.1 And form a battery. Electrochemical impedance spectroscopy tests on symmetrical batteries with BCFZYF as oxygen electrode and BZCYYbF as electrolyte support found that the material has a low area specific impedance value far exceeding that of batteries composed of undoped F materials, which means that F doping can improve the catalytic activity of the oxygen electrode and the electrolyte. The relaxation time distribution (DRT) analysis of electrochemical impedance found that F doping is beneficial to improving ion migration at the interface between the electrode and the electrolyte. The incorporation of F into the perovskite oxygen site can reduce the metal-oxygen bond energy at the B site, which is beneficial to the activity of lattice oxygen and the improvement of the migration rate of oxygen ions and protons, and this strategy can be applied simultaneously in the electrode and the electrolyte. The single cell with BCFZYF as oxygen electrode, BZCYYbF as electrolyte and Ni-BZCYYbF as hydrogen electrode support has an output power of 998mW cm at 650℃, 600℃, 550℃, 500℃ and 450℃ respectively with hydrogen as fuel. -2 , 784 mW cm -2 , 593mW cm -2 , 418 mW cm -2 , 271mW cm -2 . At the same time, the battery itself also has good performance stability and structural stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 These are the XRD patterns of BCZFYF, BCFZY, BZCYYbF, BZCYYb, the XRD refined patterns of BCFZY and BCFZYF, and the XRD test results that change with temperature.
[0019] Figure 2 These are the scanning electron microscope (SEM) and corresponding elemental analysis diagrams of BCZFYF and BZCYYbF, and the projection electron microscope (TEM) and corresponding elemental analysis diagram of BCZFYF.
[0020] Figure 3 This is a comparison chart of X-ray photoelectron spectroscopy (XPS) of BCFZYF and BCFZYX, BZCYYb and BZCYYbF.
[0021] Figure 4 Arrhenius impedance diagram and activation energy comparison diagram of symmetric batteries BCFZYF+BZCYYbF and BCFZY+BZCYYb.
[0022] Figure 5 Single cell performance diagram and impedance diagram of NiO+BZCYYbF||BZCYYbF||BCFZYF and NiO+BZCYYb||BZCYYb||BCFZY.
[0023] Figure 6 for
[0024] Figure 7 This is a comparison chart of the thermal expansion coefficient (TEC) of BCFZYF, BZCYYbF, BCFZY, and BZCYYb.
[0025] Figure 8 This is the single cell stability test diagram of NiO+BZCYYbF||BZCYYbF||BCFZYF and NiO+BZCYYb||BZCYYb||BCFZY.
[0026] Fig. 9 Comparison of IV curves of BCFZYF and BZCYYbF materials. DETAILED DESCRIPTION
[0027] The present invention relates to a proton ceramic fuel cell composed of an oxygen site F-doped perovskite electrode and an electrolyte, wherein the molecular formula of the oxygen electrode perovskite material is BaCo 0.4 Fe 0.4 Zr 0.1 Y 0.1 O 2.9-δ F 0.1 (BCFZYF), whose electrolyte perovskite material molecular formula is BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 2.9-δ1 F 0.1 (BZCYYbF), whose hydrogen electrode composition is Ni-BZCYYb, δ represents the oxygen vacancy content, and belongs to the field of solid oxide fuel cells. Among them, the incorporation of F into the perovskite oxygen site can reduce the metal-oxygen bond energy at the B site, which is beneficial to the activity of lattice oxygen and the improvement of the migration rate of oxygen ions and protons. Moreover, this strategy can be applied simultaneously in the electrode and the electrolyte to improve the ion migration at the interface between the electrode and the electrolyte. First, X-ray diffraction (XRD) combined with Rietveld refinement showed that both BCFZYF and BZCYYbF have The cubic perovskite structure of the space group has good high-temperature structural stability. Scanning electron microscopy (SEM) and projection electron microscopy (TEM) proved that the F element successfully entered the lattice and was evenly dispersed. X-ray photoelectron spectroscopy (XPS) was used to compare the original material with the F-doped material, which also proved that the F element was successfully doped into the material. Electrochemical impedance spectroscopy (EIS) test showed that the battery doped with F element had lower ohmic impedance and polarization impedance than the undoped battery. Combined with the Arrhenius equation calculation, it can be concluded that the activation energy of the reaction is reduced after F doping. Finally, the oxygen site F-doped perovskite material was applied to the oxygen electrode of the reversible solid oxide battery, and the performance of the proton ceramic fuel cell was tested with the Ni-BZCYYbF||BZCYYbF||BCFZYF single cell structure. The results showed that the output power with hydrogen as fuel reached 998mW cm at 650℃, 600℃, 550℃, 500℃ and 450℃, respectively. -2 , 784mWcm -2 , 593mW cm -2 , 418 mW cm -2 , 271mW cm -2 . At the same time, the battery itself also has good performance stability and structural stability.
[0028] Example 1 Preparation of oxygen-site F-doped perovskite electrode and electrolyte
[0029] This embodiment provides a proton ceramic fuel cell oxygen electrode BaCo 0.4 Fe 0.4 Zr 0.1 Y 0.1 O 2.9-δ F 0.1 (BCFZYF) and electrolyte BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 2.9-δ F 0.1 The preparation method of (BZCYYbF) comprises the following specific steps:
[0030] (1) Oxygen electrode: Weigh 7.498 g of barium carbonate, 1.284 g of cobalt oxide, 1.234 g of ferroferric oxide, 0.492 g of zirconium oxide, 0.451 g of yttrium oxide, and 0.350 g of barium fluoride, add these chemicals into a ball mill, add ethanol as a dispersant, and use a planetary ball mill to first perform forward milling for half an hour at a speed of 400 rpm, then stop for ten minutes, then perform reverse milling for half an hour, then stop for ten minutes, then perform forward milling for half an hour, then stop for ten minutes, and finally perform reverse milling for half an hour, for a total of two hours. After the ball milling, the solution in the ball mill jar was aspirated into a watch glass with a rubber-tipped dropper and the ethanol was dried under a sodium lamp to obtain the precursor powder of BCFZYF. The precursor powders were first calcined at 1200°C in a muffle furnace for 10 hours. After cooling, the calcined powders were ground in an agate mortar and calcined again at 1200°C in a muffle furnace for 10 hours to finally obtain the BCFZYF perovskite oxygen electrode material.
[0031] (2) Electrolyte: Weigh 5.525 g of barium carbonate, 0.369 g of zirconium oxide, 3.614 g of cerium oxide, 0.338 g of yttrium oxide, 0.591 g of ytterbium oxide, and 0.262 g of barium fluoride, add these chemicals into a ball mill, add ethanol as a dispersant, and first ball mill in a planetary ball mill at a speed of 400 rpm for half an hour in the forward direction, then stop for ten minutes, then ball mill in the reverse direction for half an hour, then stop for ten minutes, then ball mill in the forward direction for half an hour, then stop for ten minutes, and finally ball mill in the reverse direction for half an hour, for a total of two hours of ball milling time. After the ball milling is completed, the solution in the ball mill is sucked out into a watch glass with a rubber-tipped dropper, and the ethanol is dried under a sodium lamp to obtain the precursor powder of BZCYYbF, which is first calcined in a muffle furnace at 1000° C. for 10 hours.
[0032] Control experiment
[0033] The oxygen electrode and electrolyte material without F doping were prepared by adding different amounts of barium carbonate, cobalt oxide, ferrous oxide, zirconium oxide, cerium oxide, yttrium oxide and ytterbium oxide in different stoichiometric ratios according to the preparation method in Example 1 to obtain the oxygen electrode BaCo 0.4 Fe 0.4 Zr 0.1 Y 0.1 O 3-δ (BCFZY) and electrolyte BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ (BZCYYb) Comparative material.
[0034] Symmetrical battery preparation
[0035] Weigh 1g of the oxygen electrode powder BCFZYF prepared in Example 1, 10ml of isopropanol, 2ml of ethylene glycol, and 0.8ml of propylene glycol into a high-energy ball mill. After ball milling for 30min at 400 rpm, transfer it to the strain bottle with a rubber-tipped dropper to obtain the required oxygen electrode slurry. Place the prepared BZCYYbF electrolyte sheet on a heating table and preheat it at 150°C. Use a spray gun to evenly spray the prepared oxygen electrode slurry on both sides of the electrolyte under the push of nitrogen. After the liquid evaporates completely, place the sprayed electrolyte in a high-temperature muffle furnace and calcine it at 1000°C for 2h to obtain the required symmetrical battery. Note that the heating rate and cooling rate are both 3°C / min to ensure that the oxygen electrode material and the electrolyte material are tightly connected. The symmetrical battery finally obtained is used to test the impedance of the oxygen electrode material in the range of 450-650°C.
[0036] Preparation of single cell
[0037] The prepared dry-pressed battery cell is placed on a heating table and preheated at 150°C. The oxygen electrode slurry prepared in Example 1 is evenly sprayed on the electrolyte surface of the dry-pressed cell using a spray gun under the push of nitrogen. After the liquid is completely evaporated, the sprayed dry-pressed battery is placed in a high-temperature muffle furnace and calcined at 1000°C for 2 hours to obtain the required single cell. The temperature control rate is consistent with that in Example 2.
[0038] Characterization results
[0039] 1. X-ray diffraction (XRD) characterization
[0040] The XRD spectra of the four perovskite materials are shown in Figure 2. Figure 1 a and Figure 1 As shown in b, we can see that the two groups of materials BCZFYF and BCFZY, and BZCYYbF and BZCYYb show similar crystal structures, and no obvious impurity phases are found. Figure 1 d and Figure 1 e are the XRD refinement results of the comparative materials BCFZY and BCFZYF. According to the refinement results, it can be seen that BCFZYF and the comparative material BCFZY are both single-phase perovskite materials, whose space groups are Pm-3m and the lattice constants are and Figure 1 c and Figure 1 f are the XRD results of BCFZY and BCFZYF changing with temperature, which show that the phase structures of the two materials are stable in the range of room temperature to 750℃, and only normal lattice expansion is found when the temperature rises.
[0041] 2. Electron Microscopy Characterization
[0042] Scanning electron microscopy (SEM) was used to characterize BCFZYF and BZCYYbF, and transmission electron microscopy (TEM) and electron energy dispersion (EDS) element analysis were performed on BCFZYF. The results showed that the F element was successfully incorporated and the elements were evenly distributed without obvious aggregation.
[0043] 3. X-ray photoelectron spectroscopy (XPS) characterization
[0044] XPS analysis was performed on BCFZYF, BZCYYbF, BCFZY, and BZCYYb to compare the materials with and without F doping. The results showed that after F doping, XPS had an obvious peak corresponding to the F element, proving that the F element was successfully doped into the perovskite lattice.
[0045] 4. Area Specific Resistance (ASR) Test
[0046] Figure 4 The Arrhenius impedance diagrams of the symmetrical cells BCFZYF+BZCYYbF and BCFZY+BZCYYb are shown. We can clearly see the impedance differences between the four materials.
[0047] The results show that compared with the BCFZY+BZCYYb symmetric battery, the BCFZYF+BZCYYbF symmetric battery with the same electrolyte thickness has smaller ohmic impedance and polarization impedance. The activation energy of BCFZYF+BZCYYbF (75.31 kJ mol -1 ) is significantly lower than the activation energy of BCFZY+BZCYYb (90.17 kJmol -1 ). These results all indicate that the incorporation of F can enhance the oxygen catalytic activity in the bulk phase and the migration ability of hydrogen and oxygen.
[0048] 5. Distribution of relaxation time (DRT) analysis
[0049] Figure 5 The DRT analysis results of the impedance data of the symmetrical cells BCFZYF+BZCYYbF and BCFZY+BZCYYb are shown respectively. The DRT spectrum shows three different types of peaks, corresponding to three different electrocatalytic processes. 4 The impedance peak in the high frequency band around 10 Hz may be related to the ion transfer process at the electrode / electrolyte interface. 4 The impedance peak in the frequency range of -10 Hz is likely related to the ion diffusion in the bulk phase of the oxygen electrode. -2The impedance peak in the low-frequency range of Hz is attributed to the combined effect of surface ion diffusion and gas diffusion. The results show that at different temperatures, the symmetrical battery BCFZYF+BZCYYbF has lower impedance values in the high-frequency and medium-frequency bands than the symmetrical battery BCFZY+BZCYYb. This means that the simultaneous addition of F elements to electrode materials and electrolyte materials not only improves the bulk ion transport performance of electrode materials, but also improves the compatibility of electrode materials and electrolyte materials at the interface, which helps to improve the overall performance and stability of the battery.
[0050] 6. Single battery output power test
[0051] Figure 6 The output power test results of two single cells composed of F-doped materials and non-F-doped materials are shown respectively. The battery structures of the two batteries are: Ni-BZCYYbF||BZCYYbF||BCFZYF and Ni-BZCYYb||BZCYYb||BCFZY.
[0052] The peak power density (PPD) of the F-doped single cell at 650℃, 600℃, 550℃, 500℃, and 450℃ is 998mW cm -2 , 784 mW cm -2 , 593mW cm -2 , 418 mW cm -2 , 271mW cm -2 , which is significantly better than the single cell without F doping at oxygen sites (PPD at 650℃, 600℃, 550℃, 500℃, and 450℃ are 776, 566, 402, 289, and 186 mW cm, respectively). -2 ). This indicates that the battery composed of oxygen-site F-doped perovskite materials has higher hydrogen and oxygen mobility and better catalytic activity, making the battery have superior performance.
[0053] Fig. 9 The output power test results of two single cells composed of F-doped cathode on F-doped electrolyte and non-F-doped electrolyte are shown respectively. The battery structures of the two batteries are Ni-BZCYYbF||BZCYYbF||BCFZYF and Ni-BZCYYb||BZCYYb||BCFZYF. The peak power density (PPD) of the single cell with F-doped electrolyte at 650℃, 600℃, 550℃, 500℃, and 450℃ is 800mW cm -2 , 690mW cm -2 , 530mW cm -2 , 350mW cm -2 , 200mW cm -2, which is significantly better than the single cell without F-doped electrolyte (650℃, 600℃, 550℃, 500℃
[0054] The PPDs at 450℃ and 740, 560, 400, 285 and 180 mW cm -2 ). This indicates that the battery composed of oxygen-site F-doped perovskite materials has higher hydrogen and oxygen mobility and better catalytic activity, making the battery have superior performance.
[0055] 7. Thermal Expansion Coefficient (TEC) Test
[0056] Figure 7 The thermal expansion coefficients of BCFZYF, BZCYYbF, BCFZY, and BZCYYb were tested respectively. The results showed that F doping is beneficial to reducing the thermal expansion coefficient of the cathode, while increasing the thermal expansion coefficient of the electrolyte, which helps to improve the thermal expansion matching between the electrode and the electrolyte to a certain extent and improve the battery stability.
[0057] 8. Stability test
[0058] Figure 8 Two single cells composed of F-doped materials and undoped materials were heated at 550℃ and 400mAcm -2 The test voltage changes with time under constant current. The results show that the material stability is significantly improved after F doping, indicating that the battery composed of oxygen site F doped perovskite has excellent performance stability.
Claims
1. A proton ceramic fuel cell oxygen electrode perovskite material, characterized in that: Its chemical formula is BaCo 0.35+ m Fe 0.35+n Zr 0.05+x Y 0.05+y O 2.9-δ -F 0.05+z (BCFZYF), where δ is the oxygen vacancy content; 0≤m,n,x,y,z≤0.
1.
2. The method for preparing the proton ceramic fuel cell oxygen electrode perovskite material according to claim 1, characterized in that: It was prepared by solid phase method.
3. The preparation method according to claim 2, characterized in that: The solid phase method comprises the following steps: ball milling BaCO3, CO3O4, Fe3O4, ZrO2, Y2O3 and BaF2 according to a stoichiometric ratio, drying and calcining to obtain an electrode material.
4. The preparation method according to claim 2, characterized in that: The rotation speed of the ball milling process is 200-600rpm, and the calcination process parameters are: first calcining at 1100-1300°C for 5-10h, then grinding the calcined powder with a mortar, and then calcining at 1100-1300°C for 5-10h.
5. A proton ceramic fuel cell electrolyte material, characterized in that: Its chemical formula is BaZr 0.05+x Ce 0.65+p Y 0.05+ y Yb 0.1 O 2.9-δ F 0.05+z (BZCYYbF), where δ is the oxygen vacancy content; 0≤p,x,y,z≤0.
1.
6. The method for preparing the electrolyte material according to claim 5, characterized in that: It was prepared by solid phase method.
7. The preparation method according to claim 6, characterized in that: The solid phase preparation process comprises: ball milling BaCO3, ZrO2, CeO2, Y2O3, Yb2O3 and BaF2 according to a stoichiometric ratio, drying and calcining to obtain an electrolyte material.
8. The preparation method according to claim 6, characterized in that: The rotation speed of the ball milling process is 200-600rpm, and the calcination process parameters are: calcination at 1100-1300°C for 5-10h.
9. A proton ceramic fuel cell, characterized in that: The oxygen battery comprises the oxygen electrode perovskite material according to claim 1, and / or the electrolyte comprises the electrolyte material according to claim 5.
10. The proton ceramic fuel cell according to claim 9, characterized in that: In the fuel cell, the hydrogen electrode is a composite electrode material composed of NiO and the above electrolyte material; the mass ratio of NiO to the electrolyte material is 4-6:6-4.
Citation Information
Cited By
Electrolyte material and preparation method thereof, fuel cell and vehicle
CN120432583A